Analisis Yuridis Mengenai Perbuatan Melanggar Hukum Oleh Dropshipper Dalam Transaksi Jual Beli Online Melalui Platform Facebook - Saputro, Hermawan Dwi; Purwanto, Aldira Mara Ditta Caesar (Universitas Gorontalo, 2025)
The development of information and communication technology in Indonesia has grown rapidly. This development is reflected in activities such as online buying and selling. Nowadays, there are various forms of online transactions, including those that do not require stock, such as dropshipping. However, this system still causes many issues that lead to unlawful actions. This study uses a juridical-normative approach, referring to the Indonesian Civil Code (KUHPer) and the Consumer Protection Law (UUPK). The research reveals that illegal dropshipping often occurs due to the misuse of information and digital transaction systems, resulting in harm to consumers and the original product owners. The conclusion emphasizes the importance of legal measures, both litigation and non-litigation, to protect the rights of consumers and business actors who are harmed.